2019
DOI: 10.1101/2019.12.30.891200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into Functional Connectivity in Mammalian Signal Transduction Pathways by Pairwise Comparison of Protein Interaction Partners of Critical Signaling Hubs

Abstract: Growth factors and cytokines activate signal transduction pathways and regulate gene expression in eukaryotes. Intracellular domains of activated receptors recruit several protein kinases as well as transcription factors that serve as platforms or hubs for the assembly of multi-protein complexes. The signaling hubs involved in a related biologic function often share common interaction proteins and target genes. This functional connectivity suggests that a pairwise comparison of protein interaction partners of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…In contrast, Irf5 and Sp110 were the lowest-ranked nodes in the sub-network. Furthermore, transcription factors involved in a related biologic function often share common protein interaction partners and target genes as revealed by pairwise analysis of transcription factor hubs involved in innate and adaptive immunity (25). Implementing the pairwise analysis of common protein interaction partners of Stat1 and other hubs in antiviral sub-network in Biogrid database revealed that Rela and Stat3 as additional members of the extended network (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, Irf5 and Sp110 were the lowest-ranked nodes in the sub-network. Furthermore, transcription factors involved in a related biologic function often share common protein interaction partners and target genes as revealed by pairwise analysis of transcription factor hubs involved in innate and adaptive immunity (25). Implementing the pairwise analysis of common protein interaction partners of Stat1 and other hubs in antiviral sub-network in Biogrid database revealed that Rela and Stat3 as additional members of the extended network (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 by immune cells in response to respiratory virus infection resulting in the cross-talk between Stat1 and other transcription factors such Stat3, Rela, and Jun and fine-tuning of pathogen response (48). The protein interaction module of Stat1, Stat3, Rela, and Jun was shown to be a characteristic feature of innate and adaptive immunity (25)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that transcription factors of innate and adaptive immunity show functional connectivity involving shared interacting protein partners and target genes. (47). Cluster analysis revealed that Egr-1 induction was correlated with the expression of Egr-1 target genes by IFN-α/β in PBMC and in BMDM cells (Figure 7).…”
Section: Regulation Of Egr-1 Target Genes In Pbmc and Bmdm By Ifn-a /βmentioning
confidence: 92%